2019
DOI: 10.1128/aac.01844-18
|View full text |Cite
|
Sign up to set email alerts
|

High-Dosage Cefazolin Achieves Sufficient Cerebrospinal Diffusion To Treat an External Ventricular Drainage-Related Staphylococcus aureus Ventriculitis

Abstract: A patient received continuous infusion of cefazolin 10 g then 8 g daily for an external ventricular drainage-related methicillin-susceptible Staphylococcus aureus (MSSA) ventriculitis. Median free concentrations in the cerebrospinal fluid were 11.9 and 6.1 mg/liter after 10- and 8-g doses, respectively. Free concentrations in the cerebrospinal fluid were always above the MIC usually displayed by methicillin-susceptible Staphylococcus aureus (MSSA) isolates. These results support the use of high-dose cefazolin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Conversely, significant CSF accumulation and neurotoxicity were reported by others after multiple doses [ 12 ]. More recently, potentially therapeutic concentrations of cefazolin in CSF samples have been reported in less well-defined or smaller populations, though some reports rely on the low MSSA minimum inhibitory concentration (MIC) of 0.5 mg/L, which is an important caveat [ 6 , 7 , 18 , 19 ]. Of interest, 1 report used serial therapeutic drug monitoring and continuous infusion cefazolin of 10 or 8 g daily to effectively treat MSSA ventriculitis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, significant CSF accumulation and neurotoxicity were reported by others after multiple doses [ 12 ]. More recently, potentially therapeutic concentrations of cefazolin in CSF samples have been reported in less well-defined or smaller populations, though some reports rely on the low MSSA minimum inhibitory concentration (MIC) of 0.5 mg/L, which is an important caveat [ 6 , 7 , 18 , 19 ]. Of interest, 1 report used serial therapeutic drug monitoring and continuous infusion cefazolin of 10 or 8 g daily to effectively treat MSSA ventriculitis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, potentially therapeutic concentrations of cefazolin in CSF samples have been reported in less well-defined or smaller populations, though some reports rely on the low MSSA minimum inhibitory concentration (MIC) of 0.5 mg/L, which is an important caveat [ 6 , 7 , 18 , 19 ]. Of interest, 1 report used serial therapeutic drug monitoring and continuous infusion cefazolin of 10 or 8 g daily to effectively treat MSSA ventriculitis [ 6 ]. This case report found a median CSF concentration of 12 mg/L with a CSF:plasma ratio of 12% during a 10-g/d continuous infusion and a median CSF concentration of 6.1 mg/L with a CSF:plasma ratio of 10% during an 8-g/d continuous infusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frame and colleagues reported that cefazolin achieved higher concentrations in human brain tissue than did nafcillin [4]. In a patient with MSSA ventriculitis being treated with continuous intravenous infusions of high-dose cefazolin at 10 g and then 8 g daily, Gregoire et al [5] reported CSF cefazolin concentrations of 11.9 mg/L and 6.1 mg/L respectively.…”
Section: To the Editormentioning
confidence: 99%
“…Another critical consideration for cefazolin is the supposed weak meningeal diffusion and lack of central nervous system (CNS) penetration [ 9 ]. On the contrary, a recent study showed that meningeal diffusion appeared sufficient with high-dose cefazolin [ 10 ]. Similarly, findings from 1 retrospective study suggested that patients who received cefazolin had a lower risk of mortality and a similar risk of recurrent infection than those who received ASPs [ 11 ].…”
mentioning
confidence: 99%